Action of herbicides on the growth in vitro of Trichoderma and Azospirillum isolates (Research, Society and Development, 2022)
The use of microorganisms in agriculture appears as an alternative for disease control and plant growth promotion. However, the indiscriminate use of herbicides for a particular crop can compromise the soil microbiota. Therefore, the objective was to evaluate the in vitro compatibility of herbicides used in the management of soybean weeds on the growth behavior of Trichoderma asperellum and Azospirillum brasilense. A completely randomized design was used, in a 2 x 4 factorial scheme, with three replications. Factor A corresponded to herbicide doses; and factor B, to the four types of herbicides, and for the control, the cultivation of microorganisms in culture medium without addition of the herbicide solution. The assay was carried out under in vitro conditions, for the isolate T. asperellum, radial mycelial growth (CMR) and sporulation of the isolates were evaluated, and for the isolate A. asperellum, inhibition halo formation and colony forming units per milliliters were evaluated (CFU mL-1). Considering that it was not significant, the herbicides at the lowest dose affected the fungal and microbial growth of the isolates T. asperellum and A. brasilense. For both isolates, the herbicide Crucial® and Boral® showed greater interference in their growth.